Performance of grasses, shrubs and trees on disturbed soil at the AOSERP Mildred Lake Camp experimental area ... - Fedkenheuer, A. W.; Chu, C. B. (University of Alberta Library, 1980)
The plants referred to in this report were initially established on the AOSERP Mildred Lake Camp area in 1977. The objectives of the program were to establish grass, shrub and tree species for evaluation of their response, particularly their reproduction response, to the climatic and edaphic conditions north of Fort McMurray. Over the 1977 growing season, 50 species and/or sources of grasses were spring seeded, 47 species and/or sources were started in containers and transplanted to the field and 24 species and/or sources were fall seeded. In addition, 12 woody plant species and/or sources were also planted in the field after growth in the greenhouse in containers. This report discusses the results of an evaluation of the plants conducted in late August and September, 1979. ...